Impact of the Fukushima Nuclear Disaster on the Oil-Consuming Sectors of Japan. Issue Volume 16:Issues 2(2017) (4th May 2017) - Taghizadeh-Hesary, Farhad; Yoshino, Naoyuki; Rasoulinezhad, Ehsan
ABSTRACT: This research sheds light on the elasticity of oil consumption of Japan's various economic sectors and the crude oil price before and after the Fukushima disaster. To do so, the study applies a cointegration analysis and performs a vector error correction (VEC) variance decomposition by using quarterly data from Q1 1981 to Q4 2010 and from Q1 2011 to Q4 2015. The findings reveal that the absolute value of elasticities of oil consumption by some economic sectors reduced after this disaster because of increased dependency on oil consumption, which endangered energy security in the country. To raise energy self-dependency and energy security, Japan needs to diversify its energy supplies. Because renewable energy projects are mainly considered risky by banks and banks are reluctant to finance them, the paper introduces an innovative form of financing these projects: Hometown Investment Trust Funds, which was introduced and applied in Japan and in some other parts of Asia.